2002
DOI: 10.1046/j.1464-410x.2002.02901.x
|View full text |Cite
|
Sign up to set email alerts
|

Is microscopic haematuria a urological emergency?

Abstract: Patients with dipstick-positive haematuria should be re-assessed by urine microscopy before referral. As only 1.4% of patients had a malignant pathology (all noninvasive), microscopic haematuria should be regarded as a separate entity from macroscopic haematuria, and such patients do not need to be referred urgently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…However, most patients with microscopic haematuria have no urological pathology. One large study of 1950 patients found that 87.3% had no urological cause [1], which is consistent with previous studies [4,5]. How should these patients be subsequently managed?…”
Section: Introductionsupporting
confidence: 82%
“…However, most patients with microscopic haematuria have no urological pathology. One large study of 1950 patients found that 87.3% had no urological cause [1], which is consistent with previous studies [4,5]. How should these patients be subsequently managed?…”
Section: Introductionsupporting
confidence: 82%
“…In a similar study, involving 1034 Japanese adults (75% female), only two cases of bladder cancer was identified in women with microscopic hematuria [14]. Another study conducted in the UK revealed an incidence of 1.4% of bladder tumors in patients with microhematuria [15]. On the other hand, some other studies have also reported high incidences of malignancy among patients with microscopic hematuria.…”
Section: Discussionmentioning
confidence: 99%
“…57 Among 40 referral studies of patients undergoing evaluation for MH, 4 studies clearly identify 6 patients younger than 40 years with GU cancer diagnoses [58][59][60][61] (although 3 of these 4 studies do not provide specific ages) and an additional 15 studies report cancer diagnoses but do not specify whether they occurred in patients younger than 40 years. 23,[62][63][64][65][66][67][68][69][70][71][72][73][74][75] Although a handful of these studies comment on the role of cigarette smoking, none systematically account for all known GU cancer risk factors. The absence of risk factor assessment among the youngest patients with cancer is especially striking as these are the cases on which the AUA guideline bases the universal lowering of the age threshold for cystoscopy.…”
Section: Existing Guidelines and Recommendationsmentioning
confidence: 99%